Effect of individual psychoeducation for primary caregivers of children with autism on internalized stigma and care burden: a randomized controlled trial - Kaçan, Havva; Gümüş, Funda; Bayram Değer, Vasfiye (Informa UK Limited, 2023)
This study aims to determine the effects of a six-week individual psychoeducation program provided to primary caregivers of children with autism on stigma and care burden. The study was conducted with 88 primary caregivers (experimental group n = 45, control group n = 43) of children diagnosed with autism. The study, prepared in an experimental design with a pretest, posttest, and control group, was performed between 17 June 2021 and 17 January 2022. In the study, a six-week individual psychoeducation was given to the experimental group. Study data were collected using a personal information form, the Internalized Stigma of Parents in Mental Illness Scale (ISPMIS), and the Caregiver Burden Scale (CBS).The mean pretest ISPMIS total score of the experimental group was X ¯  =105.756 and the posttest total score after the psychoeducation was X ¯ =66.489,which was a significant decrease (t = 25.571; p < 0.05). The mean CBS pretest total score of the experimental group was X ¯ =61.067 and the posttest total score was X ¯ =31.667, which was a significant decrease (t = 17.499;p < 0.05). The study revealed that the six-week individual psycho education provided to primary caregivers of children with autism decreased the participants' internalized stigma and perceived care burden.
Keywords: Caregiver Burden; Children With Autism; Psychoeducation; Randomized Controlled Experiment; Primary Caregiver